Trends in suicide among adolescents aged 14–17 years in India: 2014–2019 - Vikas Arya; Gregory Armstrong; Caley Tapp; Sandersan Onie; Piumee Bandara; G. Anil Kumar; Matthew Spittal; Andrew Page; Lakshmi Vijayakumar; Jane Pirkis; Rakhi Dandona (Cambridge Prisms: Global Mental Health)
This study investigates the epidemiology of adolescent suicide in India, addressing the limited research on the subject. Data on adolescent suicide (14–17 years) by sex and state were obtained from the National Crimes Records Bureau for 2014–2019, which included acquiring unpublished data from 2016 to 2019. Crude suicide rates for the period 2014–2019 were calculated by sex and state. Rate ratios (RRs) by sex and state were also calculated to assess changes over time, comparing suicide rates from 2017–2019 to 2014–2016. Female adolescent suicide rates, which ranged between 9.04 and 8.10 per 100,000 population, were consistently higher than male adolescent suicide rates, which ranged between 8.47 and 6.24 per 100,000 population. Compared to the first half of the study period (2014–2016), adolescent suicide rates significantly increased between 2017 and 2019 among less developed states (RRs = 1.06, 95% uncertainty interval [UI] = 1.03–1.09) and among females in these states (RRs = 1.09, 95% UI = 1.05–1.14). Male suicide rates aligned with global averages, while female rates were two to six times higher than in high-income and Southeast Asian countries. Findings highlight the urgent need for comprehensive surveillance and targeted suicide prevention strategies to address this critical public health issue.